PENINGKATAN EKONOMI MASYARAKAT DESA LUBUK ENAU KECAMATAN LEMBAK KABUPATEN MUARA ENIM MELALUI POTENSI DESA - Generous Antoni (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Lubuk Enau Village, Lembak District, Muara Enim Regency. In this village, it was the Preparation Village which later became the definitive village. From Lubuk Enau - Lubuk Enau Village, Lembak District. This village was only inaugurated as a separate village in 2011 based on the regulation of the Regent of Muara Enim No. 25. In this village most of the people work as farmers. Based on the results of observations of KKN. It was found that the Lubuk Enau Village government did not explore and manage the economic potential of the MSME sector, and the potential of Natural Resources owned by Lubuk Enau Village itself. Community service activities carried out by KKN Group 4 students together with Karang Taruna Lubuk Enau Village by holding workshop activities. The goal to be achieved is that MSME actors in the village can expand their marketing reach on social media. However, one of the problems faced in the development of MSMEs in Lubuk Enau Village is the limited internet network making economic empowerment difficult.